Effects of tire wear particles with and without photoaging on anaerobic biofilm sulfide production in sewers and related mechanisms. (December 2022) - Li, Kun; Yu, Jianghua; Chen, Xingyue; Kong, Deyue; Peng, Yonghong; Xiu, Xiaojia; Su, Han; Yan, Liankang
Abstract: Tire wear particles (TWPs) are considered to be one of the major sources of microplastics (MPs) in sewers; however, little has been reported on the surface properties and photochemical behavior of TWPs, especially in terms of their environmental persistent radicals, leachate type, and response after photoaging. It is also unknown how TWPs influence the production of common pollutants (e.g., sulfides) in anaerobic biofilms in sewers. In our study, the effects of cryogenically milled tire treads (C-TWPs) and their corresponding photoaging products (photoaging-TWPs, A-TWPs) on anaerobic biofilm sulfide production in sewers and related mechanisms were studied. The results showed that the two TWPs at a low concentration (0.1 mg L −1 ) exerted no significant (p > 0.05) effects on sulfide yield, whereas exposure to a high concentration of TWPs (100 mg L −1 ) inversely affected sulfide yield, with A-TWPs exerting a significant inhibitory effect on sulfide yield in the sewers (p < 0.01). The main reason was that A-TWPs carried higher concentrations of reactive environmental persistent radicals on their surfaces after photoaging than C-TWPs, which could induce the formation of oxygen radicals. In addition, A-TWPs were more uniformly distributed in the wastewater system and could penetrate the biofilm to damage bacterial cells, and their ability to leach polycyclic aromatic hydrocarbons and heavy metals such as zinc additives enhanced their toxic effects. In contrast, C-TWPs contributed significantly to sulfide production (p < 0.01), primarily because of their low biotoxicity, ability to leach a considerable amount of sulfide, and stimulatory effect on anaerobic biofilm surface sulfate-reducing bacteria. Our study complements the toxicity studies of the TWPs particles themselves and provides insight on a new influencing factor for determining the changes in sulfide generation and control measures in sewers. Graphical abstract: Image 1 Highlights: Photoaging could promote the formation of r-EPFRs on the surface of TWPs. Photoaging could enhance the stability of TWPs in wastewater. 100 mg/L C-TWPs promoted production of anaerobic biofilms sulfide in sewer. 100 mg/L A-TWPs inhibited production of anaerobic biofilms sulfide in sewer. 100 mg/L A-TWPs inhibited SRB activity and damage anaerobic microbial cells.